New species and new records of Manota Williston from Colombia, Brazilian Amazonia, and Costa Rica (Diptera, Mycetophilidae) - Kurina O; Hippa H; Amorim DD (PENSOFT PUBL, 2022)
The following five species are described as new: Manota clava sp. n. (Colombia), Manota multilobata sp. n. (Colombia), Manota perplexa sp. n. (Costa Rica), Manota setilobata sp. n. (Colombia) and Manota subaristata sp. n. (Colombia). In addition, new records for the following 11 species are presented: Manota acuminata Jaschhof & Hippa, 2005 (Costa Rica), Manota arenalensis Jaschhof & Hippa, 2005 (Costa Rica), Manota corcovado Jaschhof & Hippa, 2005 (Costa Rica), Manota costaricensis Jaschhof & Hippa, 2005 (Costa Rica), Manota diversiseta Jaschhof & Hippa, 2005 (Colombia, Brazilian Amazonia, Costa Rica), Manota minutula Hippa, Kurina & Saaksjarvi, 2017 (Brazilian Amazonia), Manota multisetosa Jaschhof & Hippa, 2005 (Costa Rica), Manota parva Jaschhof & Hippa, 2005 (Colombia, Costa Rica), Manota pisinna Hippa & Kurina, 2013 (Brazilian Amazonia), Manota spinosa Jaschhof & Hippa, 2005 (Colombia) and Manota squamulata Jaschhof & Hippa, 2005 (Costa Rica). Distribution patterns include (1) species known only locally in Costa Rica or Colombia, (2) distributions connecting Central America to west Andes lowlands, and (3) north-west Neotropical components, extending from Central America to Brazilian Amazonia. The possible biogeographical and taxonomical context of Manota species with a widespread distribution is considered.